Radio electric asymmetric brain stimulation in the treatment of behavioral and psychiatric symptoms in Alzheimer disease - Mannu P (Dove Medical Press, 2011)
Piero Mannu1, Salvatore Rinaldi1,2, Vania Fontani1, Alessandro Castagna11Rinaldi Fontani Institute, Department of Neuro Psycho Physio Pathology, Florence, Italy; 2Medical School of Occupational Medicine, University of Florence, Florence, ItalyPurpose: Behavioral and psychiatric symptoms of dementia (BPSD) are common in Alzheimer's disease (AD) and disrupt the effective management of AD patients. The present study explores the use of radio electric asymmetric brain stimulation (REAC) in patients who have had a poor response to pharmacological treatment.Patients and methods: Eight patients (five females and three males; mean [±standard deviation] age at study baseline: 69.9 ± 3.0 years) diagnosed with AD according to the DSM-IV-TR criteria (mean onset age of AD: 65.4 ± 3.5 years) were cognitively and psychometrically assessed with the Mini-Mental State Examination (MMSE), the Activity of Daily Living (ADL), the Instrumental Activity of Daily Living (IADL), and the Neuropsychiatric Inventory (NPI), prior to and after each of 2 REAC treatment cycles.Results: Scores on the MMSE and all subscales of the NPI (frequency, severity, and distress), the ADL, and the IADL were significantly improved following the initial REAC treatment. There was further significant improvement in all measurements (with a tendency for improvement in the IADL) after the second REAC treatment cycle.Conclusion: The improvement of cognitive and behavioral/psychiatric functioning following REAC treatment suggests that this innovative approach may be an effective, safe, and tolerable alternative to pharmacological treatment of AD patients, especially in the area of BPSD. Elderly patients suffering from other types of dementia may also benefit from REAC treatment.Keywords: anxiety, depression, insomnia, behavioral and psychiatric symptoms of dementia (BPSD)